DEFINITION OF DIRECTION ON SOURCE OF ACOUSTIC RADIATION WITH USE OF ARRANGEMENTS OF REGISTRAITION OF RESILIENT WAVES ON OPTICS, VICROWAVE AND ULTRASONIC BEAMS - S. A. Dubyanskiy (Научный вестник МГТУ ГА, 2016)
The article considers the principles of defining the direction to the acoustic radiation source. The results of the research in the field of directing properties of the registrating devices when operating these beams are cited.